2015
DOI: 10.5539/res.v7n7p195
|View full text |Cite
|
Sign up to set email alerts
|

Multiculturalism: Discursive Practices

Abstract: The article investigates the problem of multiculturalism. The authors examine the discursive practices of multiculturalism in relation to the multinational, multicultural, and multiconfessional Russian society undergoing a long period of social transformation. The article analyzes the trends and processes in the space of intercultural and interethnic interaction in the world and in Russia. Historically formed modes of interaction, mutual recognition, and understanding of culturally national and culturally reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Further studies on the concept of multiculturalism show that its heuristic use usually has both a negative and a positive connotation (Bayramov et al, 2015;Glazer, 1977). In their illustration of the negative sense of multiculturalism, Huntington (2004) presents it as the monocultural hegemony of dominant cultures' values, which has commonly resulted in the discrimination, exclusion, and rejection of minorities.…”
Section: Multiculturalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies on the concept of multiculturalism show that its heuristic use usually has both a negative and a positive connotation (Bayramov et al, 2015;Glazer, 1977). In their illustration of the negative sense of multiculturalism, Huntington (2004) presents it as the monocultural hegemony of dominant cultures' values, which has commonly resulted in the discrimination, exclusion, and rejection of minorities.…”
Section: Multiculturalismmentioning
confidence: 99%
“…Likewise, Bayramov et al (2015) demonstrated through a study of transient communities in Russia that the hones of multiculturalism pointed at accomplishing dominance and recognition within the political life in contemporary Europe. In its implicit sense, it could be a conception that leads to struggle between the parties involved.…”
Section: Multiculturalismmentioning
confidence: 99%
“…Подібну кризову ситуацію, пов'язану з втратою довіри між людьми та розширенням простору їх самотності, В. Байремен називає сучасним фашизмом, який у такий спосіб символізує "суспільну формацію колективного егоїзму, який прийшов на зміну капіталізму, і який неминуче приведе до нових світових війн та до катастроф" [6]. На його думку, "фашизм виникає тоді коли люди, відчуваючи свою відособленість, прагнуть об'єднатись будь-якою, однак оскільки вони не здатні поки що об'єднатись у прагненні до смислу життя та добра, вони вимушені об'єднуватись один проти одного, возвеличуючи себе, протиставляючи себе іншій групі людей, іншій нації, саме тому любов до свого народу не повинна доводити до ненависті до інших народів" [7].…”
unclassified